A novel fixation method for panfacial fracture using an Ilizarov-type external fixator. (August 2019) - Hihara, Masakatsu; Yagura, Takuma; Takegawa, Masayasu; Kakudo, Natsuko; Morimoto, Naoki; Kusumoto, Kenji
Abstract: In general, internal plate fixation is mainly performed in order to reduce multiple facial bone fractures and rarely uses an external fixator. Although it would be ideal to successfully achieve or preserve the occlusal relationship of the upper and lower jaws, it is difficult to successfully manage multiple bone fragments in order to use them to achieve internal fixation, especially when treating a severely comminuted facial fracture. In addition, it is also important to prevent the onset of severe infection after sub-periosteal dissection, due to the presence of avascular bony fragments and an internal fixation implant which thus represents a foreign body. In order to treat extensive comminuted fracture without internal plate fixation, we performed external fixation using an Ilizarov-type external fixator. The Ilizarov-type external fixator is characterized by a few circular external structures and threaded rods. This device can be modified for use in the field of orthopedic surgery to correct three-dimensional deformities caused by fragile complicated fractures and bone defects. The advantages of the Ilizarov-type external fixator for treating panfacial fractures include a low invasiveness, utility in various fracture situations, easy adjustment of threaded rods, and a low potential cost. We herein report the first case of a severe panfacial fracture that was successfully treated using an Ilizarov-type external fixator.